Direct limit of direct system of Be-Algebras - Belleza, Hanzel N. (College of Science, University of the Philippines Cebu, 2022)
This paper deals with the notion of the direct limit of direct system of BE-algebras and investigates some of its properties. Speci cally, it presents and establishes the characterizations of direct or inductive system of BE-algebras and their limits, the direct equivalence relation, the existence and uniqueness of the direct limit of direct system of BE-algebras, and co nal subsystem of direct systems of BE-algebras.